Field efficacy of botanical, biocontrol agents and pesticides against foliar diseases of cotton - Bhattiprolu, S L (Indian Journal of Plant Protection, 2020)
Efficacy of botanical product, 'EZEE Cotton' was tested at two doses of 1 ml/l and 2 ml/l in comparison with propiconazole (0.1%), acephate 2 g/l and biocontrol agents, Pseudomonas fluorescens and Trichoderma viride,each treated at 10 g/kg seed and foliar application @ 0.1% at Regional Agricultural Research Station, Lam,Guntur, during Kharif 2012 and 2013 against fungal diseases of cotton. EZEE Cotton at 2 ml/l was on par with 0.1% propiconazole in controlling Alternaria leaf spot and rust. Between the doses, EZEE Cotton at 2 ml/l gave better control of both the diseases. EZEE Cotton gave maximum disease control of 73.4% followed by propiconazole (71.8%). T. viride ST 10 g/kg and FS 1% as well as propiconazole 0.1% gave maximum control of rust (69%). Propiconazole 0.1% and T. viride increased the yield to the tune of 42.8% followed by EZEE Cotton at 42.3%. Highest Benefit Cost Ratio (BCR) of 1.43 was obtained with T. viride followed by propiconazole (1.42) and EZEE Cotton (1.41). Maximum incremental benefit cost ratio (IBCR) of 9.48 was also obtained with T. viride and P. fluorescens was the next best with 7.45 IBCR, while propiconazole recorded 6.46 IBCR. Higher cost of EZEE Cotton resulted in lower IBCR. Based on the results obtained, it is concluded that EZEE Cotton is effective against cotton diseases including Alternaria leaf spot and rust and thus can be part of integrated disease management of cotton.